Justice in private law and extracontractual civil liability for non-patrimonial damage in peruvian jurisprudence - Herrera Pérez, Enlil Iván (2019)
What does Tort Law seek through civil liability? Just deterrence? Punish the tortfeasor? Compensate the victim? The answers may be different according to certainly point of view, nevertheless we asked ourselves: what is “fair” in the civil liability context? Under that motivation, we tried to answer the following questions: is the way of justice suitable as is applied in non-economic loss cases in the Peruvian case law? And for that purpose, (i) we developed a philosophical framework about justices in this context, (ii) we described the legal doctrine and regulation framework, and (iii) we analyzed the criteria adopted in the Peruvian case law. Thus, through a systematic and dogmatic methods of interpretation, we reached a worrying conclusion: a suitable way of justice is not applied in Peruvian case law of non-economic loss in the context of Tort Law.